2015
DOI: 10.1016/j.febslet.2015.10.034
|View full text |Cite
|
Sign up to set email alerts
|

GroEL to DnaK chaperone network behind the stability modulation of σ32 at physiological temperature in Escherichia coli

Abstract: Edited by Stuart Ferguson Keywords:Stability of r 32 Physiological temperature DnaK GroEL Chaperone network E. coli a b s t r a c tThe stability of heat-shock transcription factor r 32 in Escherichia coli has long been known to be modulated only by its own transcribed chaperone DnaK. Very few reports suggest a role for another heat-shock chaperone, GroEL, for maintenance of cellular r 32 level. The present study demonstrates in vivo physical association between GroEL and r 32 in E. coli at physiological temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The experiment was done according to the protocol of [34]. NP-treated cells (seeded at 1×10 6 cells/65 mm Petri-plate) were washed three timeswith ice-cold PBS and finally suspended in 600 μl ice-cold 1X RIPA lysis buffer (abcam, Cambridge, UK) supplemented with protease inhibitor cocktail (abcam).…”
Section: Detection Of Caspase-3 By Thewestern Blot Methodmentioning
confidence: 99%
“…The experiment was done according to the protocol of [34]. NP-treated cells (seeded at 1×10 6 cells/65 mm Petri-plate) were washed three timeswith ice-cold PBS and finally suspended in 600 μl ice-cold 1X RIPA lysis buffer (abcam, Cambridge, UK) supplemented with protease inhibitor cocktail (abcam).…”
Section: Detection Of Caspase-3 By Thewestern Blot Methodmentioning
confidence: 99%
“…This does not necessarily require, however, that both chaperones act in a defined order to fold proteins, as DnaK may backup post-translationally if TF does not sufficiently function cotranslationally. Additionally, DnaK can cooperate bidirectionally with the chaperonin GroEL/ES, which is also an ATP-controlled chaperone [94][95][96].…”
Section: Box 1 Pqc: Maintaining Proteostasis In the Cellmentioning
confidence: 99%
“…At 44 °C, ramFexpressing cells grew identically to control cells (P=0.18, t-test), whereas at 30 °C ramF expression caused a severe growth reduction (P=1.27x10 -5 , t-test). This temperature-dependent phenotype further indicated that ramF activity may depend on protein homeostasis pathways as chaperone levels are often temperature-dependent [35][36][37][38][39][40][41] .…”
Section: Ramf Interacts With Chaperones To Remodel Protein Homeostasi...mentioning
confidence: 95%